Core Mycobiome and Their Ecological Relevance in the Gut of Five Ips Bark Beetles (Coleoptera: Curculionidae: Scolytinae) - Chakraborty, Amrita; Modlinger, Roman; Ashraf, Muhammad Zubair; Synek, Jiří; Schlyter, Fredrik; Roy, Amit (Frontiers in Microbiology, 2020)
Bark beetles are destructive forest pests considering their remarkable contribution to forest depletion. Their association with fungi is useful against the challenges of survival on the noxious and nutritionally limited substrate, i.e., conifer tissues. Fungal symbionts help the beetles in nutrient acquisition and detoxification of toxic tree secondary metabolites. Although gut is the prime location for food digestion and detoxification, limited information is available on gut-mycobiome of bark beetles. The present study screened the gut-mycobiont from six bark beetles (five Ips and one non-Ips) from Scolytinae subfamily using high-throughput sequencing and explored their putative role in symbiosis with the host insect. Results revealed the predominance of four fungal classes- Sordariomycetes, Saccharomycetes, Eurothiomycetes, and Dothidomycetes in all bark beetles. Apart from these, Agaricomycetes, Leothiomycetes, Incertae sedis Basidiomycota, Tremellomycetes, Lecanoromycetes, and Microbotryomycetes were also documented in different beetles. Five Ips bark beetles share a consortium of core fungal communities in their gut tissues consisting of 47 operational taxonomic units (OTUs) belonging to 19 fungal genera. The majority of these core fungal genera belong to the phylum Ascomycota. LEfSe analysis revealed a set of species-specific fungal biomarkers in bark beetles. The present study identified the gut mycobiont assemblage in bark beetles and their putative ecological relevance. An enriched understanding of bark beetle-fungal symbiosis is not only filling the existing knowledge gap in the field but may also unleash an unforeseen potential for future bark beetle management.